Workplace Incivility and Employee Performance: Does Trust in Supervisors Matter? (A Dual Theory Perspective) - Farida Saleem; Muhammad Imran Malik; Iqra Asif; Awais Qasim (Behavioral Sciences, 2022)
Employee performance is the backbone of achieving competitiveness and sustainability. This study aims to examine the impact of workplace incivility on employee performance. In addition, trust in supervisors is examined as a mediator. The conservation of resources (COR) theory and Maslow’s hierarchy of needs theory provided the grounds for developing the framework. The data were collected through closed-ended questionnaires and were analyzed using structural equation modeling with SmartPLS. The results affirmed that incivility is harmful to the performance of employees, and that trust in supervisors helps employees to perform well. The trust in the supervisor significantly mediates the incivility–performance relationship. The examination of the proposed model through the lens of two theories as well as the study of low-intensity deviant workplace behavior in a collectivist and developing economy are the contributions of this study to the growing body of literature. However, the use of a single sector was one of the limitations of this study.